2018
DOI: 10.33137/cpoj.v1i2.32048
|View full text |Cite
|
Sign up to set email alerts
|

Adjustable Liners and Sockets for Prosthetic Devices

Abstract: INTRODUCTION Ras  Labs’ Synthetic  Muscle™  will  allow  amputees  to  continue  their  active  lives  without  needing  to adjust the fitting of their prosthetic device(s) throughout the day.  This technology promises to resolve major  issues  facing  amputees,  most  notably  the  pain  of  prosthetic  slippage  and  tissue  breakdown. Synthetic  Muscle™,  comprising  electroactive  polymers  (EAPs),  actively  expand  or  contract  at  low voltages, while offering impact resistance and pressure sensin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…However, the requirement of easy handling is in opposition to this, as it is necessary to don/doff the prosthesis. In the literature [18,29,[54][55][56][57][58], a trend towards automatic compensation is emerging. Automatic adjustment is also seen as being beneficial by the orthopedic technicians.…”
Section: Discussionmentioning
confidence: 99%
“…However, the requirement of easy handling is in opposition to this, as it is necessary to don/doff the prosthesis. In the literature [18,29,[54][55][56][57][58], a trend towards automatic compensation is emerging. Automatic adjustment is also seen as being beneficial by the orthopedic technicians.…”
Section: Discussionmentioning
confidence: 99%
“…Work is underway developing electroactive polymer (EPA) networks capable of actively expanding or contracting at low voltages, offering impact resistance and pressure sensing. 99 It has been suggested that EPA can be used in liners or sockets for automatic socket volume adjustment. 99 Also, a ferrous polymer can be used as an inductive sensor (0.50 mm thickness) and as a magnetically permeable target to measure socket wall and liner distance, and decrease socket volume by approximately 2.1%.…”
Section: Management Of Residual Limb Volume Fluctuationmentioning
confidence: 99%
“…99 It has been suggested that EPA can be used in liners or sockets for automatic socket volume adjustment. 99 Also, a ferrous polymer can be used as an inductive sensor (0.50 mm thickness) and as a magnetically permeable target to measure socket wall and liner distance, and decrease socket volume by approximately 2.1%. 100 Overall, VASS with a controller and the active panel socket with an in-socket sensor appear to be viable clinical options for management of diurnal residual limb volume fluctuation; though, further developments are needed to make them commercially available.…”
Section: Management Of Residual Limb Volume Fluctuationmentioning
confidence: 99%